Young Mothers’ Trust of Celebrities and Influencers for Food Safety and Nutrition Information - Quisto Settle; Linnea Harvey; Taylor Ruth; Joy N. Rumble (Journal of Applied Communications, 2023)
Because mothers are the primary grocery shoppers for most households, they play a fundamental role in the food their families eat. As such, it is important to understand their perceptions of potential sources of food safety and nutrition information. This study surveyed young mothers (i.e., 18-40 years old) across the United States to assess their awareness, knowledge, and trust of celebrities and social media influencers who communicate about food-related topics. The list of celebrities and influencers consisted of TV chefs, celebrities and influencers who espouse favorable viewpoints of food and agriculture, and celebrities and influencers who espouse more alternative viewpoints of food and agriculture. Respondents were usually more aware and knowledgeable of the celebrities and chefs than the influencers. They also generally trusted the TV chefs the most. There tended to be small-to-medium positive correlations between a respondents’ knowledge of a celebrity/influencer and their trust of that celebrity/influencer but not all were statistically significant. Communicators looking to influence the largest number of people would benefit more from working with celebrities, but social media influencers could still play a role in campaigns that target specific online communities where the influencers’ values align with community members. More research is recommended to expand to other audiences, as well as assessing other celebrities and influencers. Research can also address how consumers use social media to get food-related information, how trust could be affected by communication using different social media platforms, and content analyses of food-related communication by celebrities and influencers on social media outlets.
Keywords: Mothers; trust; celebrities; influencers; Elaboration Likelihood Model